Proposal to Improve Employee Engagement at PT Telekomunikasi Indonesia, Tbk - Prananta, Josia; Gustomo, Aurik (The Indonesian Journal of Business Administration, 2013)
PT. XYZ transformed into T.I.M.E.S. Company in 2009. This transformation were done to maintain their position as market leader in telecommunications industry. PT. XYZ also transform their organization to support this transformation.Based on survey results XYZ Employee Survey in 2011, the employee satisfaction level in PT. XYZ was categorized high but, this achievement is not supported by the company’s performance. Based on PT. XYZ’s internal report in 2011, only 9 of 69 T-lab areas that able to meet their performance targets. This survey report was confirmed by Theme O Meter (TOM) survey in 2011, that show the level of XYZ’s 5C application is hasn’t meet the corporate target. According to Daft (2009), this condition is caused by ineffective organization. According to Right Management (2010), The organization effectiveness can be enhanced by increasing the level of employee engagement.This research focused on measuring the level of employee engagement in newly transformed unit at PT. XYZ by using a questionnaire survey that composed using the combination of several theories that related with the employee engagement theory.  The questionnaire analysis result show that the most influencing factor to employee engagement is the collaborative innovation factor. Therefore the optimization of collaborative innovation needs to be done. Based on further analysis result, PT. XYZ is suggested to redesign the Theme O Meter (TOM) assessment question, apply the TOM assessment result as the leader’s KPI, and improve the method and the weight of the score in 360o assessment to optimize the collaborative innovation culture.  Keywords: PT. XYZ, employee engagement,collaborative innovation